Longitudinal Aerodynamic Characteristics of Ducted Fan Propelled Fixed-Wing VTOL Aircraft Hovering in Ground Effect - Yanxiong Zhao; Yun Tian; Zhiqiang Wan (Aerospace, 2023)
The aerodynamic performances and control characteristics of vertical takeoff and landing aircraft will be significantly affected by the ground effect during takeoff and landing. The longitudinal aerodynamic characteristics and main flow features of a fixed-wing vertical takeoff and landing aircraft hovering in ground effect are investigated in this paper, using Multiple Reference Frame based numerical simulations. The aircraft is propelled by three ducted fans. Results show that the overall morphology of the flow is characterized by a fountain, ground vortex, reingestion, and recirculation. When the thrust distribution between the front and aft ducted fans changes, the flow features change as well. As the aircraft approaches the ground, the ducted fan thrust decreases, the fuselage lift increases, and the total lift first decreases and then increases. The maximum lift increases by 9.6% and the minimum lift decreases by 3.0% compared with that out-of-ground effect. The magnitude of the drag is about 1% of the lift, which has little influence on the aircraft’s performance. The pitching moment gradually changes from the equilibrium state to a significant nose-up moment. The total power consumed increases at a specific rotational speed.